2020
DOI: 10.1002/cctc.202001669
|View full text |Cite
|
Sign up to set email alerts
|

n‐Butyllithium Catalyzed Hydroboration of Nitriles and Carbodiimides

Abstract: Highly efficient and selective hydroboration of nitriles and carbodiimides with pinacolborane (HBpin) is achieved by using the simple and convenient n‐BuLi as a catalyst. Solvent‐free and good functional group tolerance under mild conditions have been achieved. A possible mechanistic pathway of the n‐BuLi catalyzed hydroboration of nitriles with HBpin is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Analogous studies in tetrahydrofuran were proposed to result in a complex equilibrium between several different boron-containing species in which the trialkoxy­borohydride, [( t BuO)­B­(H)­pin] − , was the major species participating in hydride delivery (Scheme ). On the basis of this precedent, a number of closely related studies have been described during the last decade, derived variously from the use of NaOH, n BuLi, (also imines, alkynes, nitriles, and carbodiimides), , NaH, KH, Li­[O t Bu], K­[O t Bu], K 2 CO 3 , KCH 2 Ph, M­[N­(SiMe 3 ) 2 ] (M = Li, Na, K), LiBr, , MF (M = K, Cs), 2,6-di- tert -butylphenolate lithium, 1,1-dilithioferrocene, ( Dipp Nacnac)­Li, and l-lithio-2-alkyl-1,2-dihydropyridine . In a very recent advance, Newman and Melen have shown that the simple bases, lithium di- iso -propylamide and tert- butoxide catalyze the hydroboration of ketones, but with some enantioselectivity (er up to 70:30) when used in conjunction with enantiopure BINOL-type ligands .…”
Section: Molecular Hydrides Of the Group 1 Metalsmentioning
confidence: 99%
“…Analogous studies in tetrahydrofuran were proposed to result in a complex equilibrium between several different boron-containing species in which the trialkoxy­borohydride, [( t BuO)­B­(H)­pin] − , was the major species participating in hydride delivery (Scheme ). On the basis of this precedent, a number of closely related studies have been described during the last decade, derived variously from the use of NaOH, n BuLi, (also imines, alkynes, nitriles, and carbodiimides), , NaH, KH, Li­[O t Bu], K­[O t Bu], K 2 CO 3 , KCH 2 Ph, M­[N­(SiMe 3 ) 2 ] (M = Li, Na, K), LiBr, , MF (M = K, Cs), 2,6-di- tert -butylphenolate lithium, 1,1-dilithioferrocene, ( Dipp Nacnac)­Li, and l-lithio-2-alkyl-1,2-dihydropyridine . In a very recent advance, Newman and Melen have shown that the simple bases, lithium di- iso -propylamide and tert- butoxide catalyze the hydroboration of ketones, but with some enantioselectivity (er up to 70:30) when used in conjunction with enantiopure BINOL-type ligands .…”
Section: Molecular Hydrides Of the Group 1 Metalsmentioning
confidence: 99%
“…In addition, high chemoselectivity of imine over nitrile reduction was observed under this procedure. 137 Very recently in 2022, Mandal group reported a Bicyclic (alkyl)(amino)carbene (BICAAC) catalyst in metal free and solvent free hydroboration of nitriles. A wide scope of substrates including aromatic, heteroaromatic, and aliphatic nitriles (40 examples) were studied using 5 mol% catalyst with 30-92% isolated yield as ammonium salt.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…In the same year of 2021, Ma and Yang reported n-BuLi as catalyst in monohydroboration of carbodiimides under neat condition at 80 °C. Both aliphatic and aromatic carbodiimides (3 examples) underwent reduction with yield of 97-99% within 24-48 h. 137 The Sen group reported lithium complexes, 2,6-di-tert-butyl phenolate lithium and 1,1′-dilithioferrocene (Fig. 12k) in carbodiimide hydroboration in 2021.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
See 2 more Smart Citations